MiR-372-3p Functions as a Tumor Suppressor in Colon Cancer by Targeting MAP3K2 - Li, Yana; Li, Fuqiang; Feng, Chang; Wu, Tingting; Chen, Yuyang; Shah, Junaid Ali; Wang, Fei; Cai, Yong; Wang, Jianfeng; Jin, Jingji (Frontiers in Genetics, 2022)
MicroRNAs (miRNAs) as small non-coding RNA transcripts bind their complementary sequences in the 3′-untranslated region (3′-UTR) of target messenger RNAs (mRNAs) to regulate their expression. It is known that miR-372 belongs to the miR-371–373 gene cluster and has been found to be abnormally expressed in a variety of cancers, but its precise mechanism in cancer remains to be discovered. In this study, miR-372-3p expression was assessed in 153 frozen tissue samples, including primary diagnosed colon cancer and matched normal and adjacent tissues, using real time quantitative polymerase chain reaction (qPCR). An analysis of qPCR data revealed a significant reduction in miR-372-3p expression (by >2-fold) in colon cancer tissues in 51.5% (34/66) of patients. Consistent with this, mimicking the increased miR-372-3p levels in SW480 colon cancer cells significantly suppressed cell growth and proliferation. Although no direct correlation was found between the low level of miR-372-3p and certain tumor-related factors, such as p53, HRE-2, PMS2, MLH1, MSH2, MSH6, HDAC4, p21, and Wee1, in colon cancer tissues, an inverse relationship between miR-372-3p and Ki67 (a marker of proliferation) or miR-372-3p and MAP3K2(MEKK2), which plays a critical role in the MAPK signaling pathways, was confirmed using tissue samples. The target relationship between miR-372-3p and MAP3K2 was verified using luciferase assays in SW480 colon cancer cells. As expected, miR-372-3p mimics significantly suppressed the luciferase activity of pMIR-luc/MAP3K2 3′-UTR in cells, suggesting that miR-372-3p modulates the expression of MAP3K2 by directly targeting its 3′-UTR. Overall, the results obtained herein suggest that miR-372-3p may function as a tumor-suppressor miRNA in colon cancer by targeting MAP3K2.